1995
DOI: 10.1063/1.1145666
|View full text |Cite
|
Sign up to set email alerts
|

Development of a hard x-ray imaging microscope

Abstract: A hard x-ray imaging microscope based on a phase zone plate has been developed and tested. The zone plate, with a 5 cm focal length and a 0.2 pm smallest linewidth, was used to image 8 keV x rays from the samples. The imaging microscope can be used to obtain nearly diffraction-limited resolution over the entire imaging field, and its resolution is almost independent of source size and source motions. We have tested such an imaging microscope, and a resolution of about 0.4 pm was obtained. The images were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…A number of methods have been developed, most notably one termed 3DXRD at the European Synchrotron radiation facility (ESRF), in collaboration with the Risø National Lab 113 and another at the Applied Photon Source (APS). 114 5 Landmark achievements in focussing for soft Fresnel zone plates (FZPs), 69,[82][83][84][85][86][87][88][89] hard FZPs, 72,[89][90][91][92][93][94] Kirkpatrick-In the former a small, usually letter-box shaped, monochromatic beam is sent through a sample and, as in absorption tomography, the sample is rotated around an axis perpendicular to the beam. Each irradiated grain diffracts part of the incident beam.…”
Section: Crystal Grain Imagingmentioning
confidence: 99%
“…A number of methods have been developed, most notably one termed 3DXRD at the European Synchrotron radiation facility (ESRF), in collaboration with the Risø National Lab 113 and another at the Applied Photon Source (APS). 114 5 Landmark achievements in focussing for soft Fresnel zone plates (FZPs), 69,[82][83][84][85][86][87][88][89] hard FZPs, 72,[89][90][91][92][93][94] Kirkpatrick-In the former a small, usually letter-box shaped, monochromatic beam is sent through a sample and, as in absorption tomography, the sample is rotated around an axis perpendicular to the beam. Each irradiated grain diffracts part of the incident beam.…”
Section: Crystal Grain Imagingmentioning
confidence: 99%
“…Moreover, in synchrotron μ-XRF analysis, the intensity and clarity of the fluorescence depend on the varied beam current intensity of X-ray with scanning time and the differences in size of the beam and the distance between detector and sample (Lai et al 1995). The relative quantitative changes in metals distributed on the samples can be determined if the scan conditions are the same.…”
Section: Discussionmentioning
confidence: 98%
“…The resolution of the presently used detector systems, based on a scintillating screen optically coupled to a CCD camera, is restricted by the scintillator properties, optical light transfer, and charge-coupled device granularity, which impose a practical limit of about 1 mm spatial resolution at detector efficiencies of a few percent (Koch et al, 1998). Different approaches have been proposed for trespassing the micrometer barrier and Fresnel zone plates (Lai et al, 1995) or parabolic compound refractive lenses (Schroer, 2002a), have demonstrated to reach sub-micrometer resolution (0.3 mm) but with sufficient efficiency only at energies well below 20 keV. A recently developed detector, installed at the Materials Science Beamline 4S of the Swiss Light Source, achieves a breakthrough in this respect, satisfying the research requirements that ask for an efficient advance towards the submicron range with high energies.…”
Section: Introductionmentioning
confidence: 99%